2021
DOI: 10.2147/jaa.s342495
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Study Assessing Risk Factors and Aeroallergens Sensitization Characteristics in Children with Self-Reported Allergic Rhinitis in China

Abstract: Background: Up to now, epidemiological studies on allergy rhinitis (AR) have primarily focused on determining the risk of disease in Chinese adults, with the majority of them designed by single centers, while cross-sectional and epidemiological data describing allergic sensitization in children with self-reported AR are scarce. Objective: This study was estimating of the latest information about the sensitization patterns and risk factors of clinical AR to develop effective strategies for the prevention and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…16 In this study, a total of 2377 patients with suspected allergic diseases from 11 provinces in China were enrolled for full quantitative sIgE detection of furry animal allergen including cat, dog and horse. Consistent with the literature, 15,18 this research found that cat dander was the predominant furry animal allergen in patients with suspected allergic disease, followed by dog and horse dander. Despite a significant increase in the prevalence of animal allergy, the results of this study showed that patients were mainly at low levels of sensitization (class 1-3).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…16 In this study, a total of 2377 patients with suspected allergic diseases from 11 provinces in China were enrolled for full quantitative sIgE detection of furry animal allergen including cat, dog and horse. Consistent with the literature, 15,18 this research found that cat dander was the predominant furry animal allergen in patients with suspected allergic disease, followed by dog and horse dander. Despite a significant increase in the prevalence of animal allergy, the results of this study showed that patients were mainly at low levels of sensitization (class 1-3).…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with the literature, 15 , 18 this research found that cat dander was the predominant furry animal allergen in patients with suspected allergic disease, followed by dog and horse dander. Despite a significant increase in the prevalence of animal allergy, the results of this study showed that patients were mainly at low levels of sensitization (class 1–3).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“… 3 Previous studies have reported that house dust mite are common in the southern and eastern areas of China, 14 while pollen allergies are prevailing in the western and northern China. 15 , 16 In this study, we recruited all qualified patients with allergies from 13 medical centers that are distributed to four regions of China, including south, north, west and east areas. A total of 18 common allergens which covered house dust mite, german cockroach, aspergillus fumigatus, penicillium and 14 grass pollen allergens were utilized to perform SPT.…”
Section: Introductionmentioning
confidence: 99%
“… 25 A multicenter study reported the most common allergens in Eastern China to be D. farinae (74.9%) and D. pteronyssinus (74.3%), while in the West, they were mugwort (60.0%) and marguerite (56.6%). 26 The most common allergens in South China are house dust mites (28.1%), cockroaches (24.3%), shrimp (19.2%), crabs (15.5%), and egg whites (9.9%). 27 An analysis of allergen-specific IgE in serum samples from individuals based in Guangzhou, Southern China, revealed that D. pteronyssinus (85.0%) had the highest proportion of specific IgE, followed by D. farinae (83.5%), egg whites (19.3%), milk (14.6%), German cockroaches (14.2%) and ox-eye daisy (12.6%).…”
Section: Ar Allergens In Chinamentioning
confidence: 99%